Dr. C. Oscar Beto Alonso Chil: an example of dedication to the Cuban medicine - Ildre Irian Dávila Rodríguez; Ariadna González Martín; Elizabeth Azopardo Núñez (Revista Habanera de Ciencias Médicas)
Oscar Beto Alonso Chil, PhD in Medicine, graduated as a Doctor of Medicine in 1954, being one of the physicians who did not leave the country after the triumph of the Revolution. He dedicated his whole life to the development of his specialty, Internal Medicine, achieving the second degree of specialization. He was a tireless researcher who devoted his life and knowledge to set the name of the Cuban Medicine at a very high level during his participation in prestigious National and International events, as a member of very important organizations and associations both inside and outside the country, and carrying out the supervision of investigations with excellent results. He was nominated for the category of academician of the Cuban Academy of Sciences. Equally important was his teaching work as a full professor of the University of Medical Sciences of Havana, Professor Emeritus and Consultant. In the course of his teaching life he was the tutor of numerous undergraduate and postgraduate studies of his specialty.